Crystalline phase impurity analysis method
The X-ray diffraction pattern of powder X-ray diffraction of the cyclic zirconium silicate sample was detected by X-ray diffraction method. Combined with standard curves or standard equations, the problem that the prior art cannot effectively detect crystal phase impurities in cyclic zirconium silicate is solved, and high precision and high sensitivity detection effect is achieved.
Patent Information
- Application Number
- CN202510168497.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-17
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art cannot effectively detect the content of crystal phase impurities such as crystal phase impurities A (CPA) and crystal phase impurities B (CPB) in sodium zirconium silicate (SZC), resulting in the impact of the efficacy of the drug.
X-ray diffraction method (PXRD) was used to obtain the powder X-ray diffraction pattern of the sample of zirconium silicate to be tested, and the content of crystal phase impurities in the sample was accurately detected in combination with standard curves or standard equations.
It realizes the simple, fast and accurate detection of the content of crystal phase impurities in sodium zirconium silicate, and has the advantages of wide linear range, good linear relationship, high precision, good durability and high detection sensitivity.
Smart Images

Figure CN119643609A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of analytical chemistry, and in particular to an analytical method for crystalline impurities. Background Art
[0002] Hyperkalemia is a common electrolyte disorder in patients with chronic kidney disease (CKD), heart failure (HF) and / or diabetes, which can damage the patient's neuromuscular and gastrointestinal functions and cause arrhythmias, which can be life-threatening. Persistent hyperkalemia in CKD patients is associated with increased all-cause mortality, and hyperkalemia in HF hospitalized patients is associated with increased short-term and long-term mortality.
[0003] Existing drugs for treating hyperkalemia are drugs used to increase gastrointestinal potassium excretion, including sodium polystyrene sulfonate (SPS), calcium polystyrene sulfonate (CPS), and Patiromer (Veltassa™). Patiromer is a relatively new therapeutic potassium-binding resin. SPS and CPS are only approved for short-term treatment of hyperkalemia, but they are non-specific and may cause hypomagnesemia, hypocalcemia, sodium excess, etc. Related drug-drug interactions limit their combined use with other drugs. Therefore, there is still an unmet clinical need for new oral drugs that can quickly and specifically reduce blood potassium and maintain normal blood potassium levels and have acceptable safety characteristics.
[0004] Sodium Zirconium Cyclosilicate (Lokelma ® SCZ (SZC) is an AstraZeneca-developed drug for the treatment of hyperkalemia in adults. It was approved for marketing in the EU and the United States in 2018, approved for domestic import in 2019, and launched in Japan in 2020. The dosage form is a powder. SCZ is a non-absorbable and insoluble non-polymer inorganic crystalline powder with a uniform microporous structure. It is a highly selective inorganic cation exchanger that captures potassium in the intestine in exchange for sodium and hydrogen ions and excretes it from the body through feces, thereby reducing excess blood potassium and correcting hyperkalemia. The powder has a high affinity for potassium ions and is not affected by the presence of other cations (such as calcium and magnesium ions). Potassium ion exchange starts in the upper digestive tract and exists throughout the gastrointestinal tract. SCZ has a cubic unit cell structure composed of corner-sharing Zr-coordinated octahedrons [ZrO6] 2- and Si coordinated tetrahedron [SiO4] 0 The units are composed of 1:3 in molar ratio. The two types of units are interconnected by oxygen bridges Zr-O-Si and Si-O-Si and are arranged repeatedly in an orderly manner to form the three-dimensional lattice characteristics of the compound. The basic expression of SCZ is Na2ZrSi3O9·nH2O (n=2~3), and the partially protonated form is Na ~1.5 H ~0.5ZrSi3O9·nH2O (n=2~3), the theoretical molecular weight range is 390.5~408.5 Daltons.
[0005] SCZ is prepared by a hydrothermal synthesis process using sodium hydroxide, colloidal silica, zirconium acetate and purified water under high temperature and high pressure conditions. In the synthesis process of SCZ, crystalline impurities such as crystalline impurity A (CPA) and crystalline impurity B (CPB) may be generated due to insufficient stirring. Unlike SCZ's highly specific exchange of potassium ions, CPA has no selectivity for the exchanged ions, and CPB has a small exchange capacity for potassium (<1mEq / g). The presence of CPB will reduce the potassium exchange capacity (KEC) of SCZ, thereby affecting the efficacy. However, there is currently no published literature reporting methods for detecting crystalline impurities such as CPA and CPB in SCZ. Summary of the invention
[0006] The object of the present invention is to provide a method for analyzing crystalline impurities. The method provided by the present invention can simply, quickly and accurately detect the content of crystalline impurities such as CPA and CPB in sodium zirconium cyclosilicate.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for analyzing crystalline impurities, comprising the following steps: Obtaining an X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested; According to the standard curve or standard equation of the crystalline phase impurities and the X-ray diffraction spectrum of the sodium zirconium cyclosilicate sample to be tested, the content of the crystalline phase impurities in the sodium zirconium cyclosilicate sample to be tested is obtained; The standard curve is obtained by fitting according to the ratio of the mass of crystalline impurities and sodium zirconium cyclosilicate in the standard curve sample, and the ratio of the diffraction intensity of the crystalline impurities and the characteristic diffraction peak of sodium zirconium cyclosilicate in the X-ray diffraction spectrum of the standard curve sample; the standard equation is the linear equation corresponding to the standard curve; The standard curve sample is a mixture of a blank sodium zirconium cyclosilicate sample and a crystalline impurity reference substance.
[0008] Preferably, the sodium zirconium cyclosilicate sample to be tested is a powder sample, and the X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested is a powder X-ray diffraction pattern. The method for obtaining the powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested comprises: scanning the powdered sodium zirconium cyclosilicate sample to be tested by an X-ray diffractometer to obtain the powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested; The standard curve sample is a powdered sample, and the X-ray diffraction pattern of the standard curve sample is a powder X-ray diffraction pattern. The method for obtaining the powder X-ray diffraction pattern of the standard curve sample includes: using an X-ray diffractometer to scan the powdered standard curve sample to obtain the powder X-ray diffraction pattern of the standard curve sample.
[0009] Preferably, the crystalline phase impurities include crystalline phase impurities A and / or crystalline phase impurities B; when analyzing the crystalline phase impurities A, the 2θ angle range of the scan is 1~25°; when analyzing the crystalline phase impurities B, the 2θ angle range of the scan is 10~20°.
[0010] Preferably, when scanning is performed under the detection conditions of the crystalline phase impurity A, the characteristic diffraction peak 2θ angles of the crystalline phase impurity A include 6.6°±0.2°, and the characteristic diffraction peak 2θ angles of sodium zirconium cyclosilicate include 11.9°±0.2°, 13.8°±0.2°, 15.5°±0.2° and 17.0°±0.2°.
[0011] Preferably, when scanning is performed under the detection conditions of the crystalline phase impurity B, the characteristic diffraction peak 2θ angles of the crystalline phase impurity B include 14.6°±0.2°, and the characteristic diffraction peak 2θ angles of sodium zirconium cyclosilicate include 13.9°±0.2° and 15.5°±0.2°.
[0012] Preferably, the scanning conditions include: using a Bruker D8 X-ray diffractometer, adopting a Cu Kα target, a tube voltage of 40.0 kV, a tube current of 40.0 mA; a pre-Sola slit of 4.1°, a secondary Soller slit of 4°, a divergence slit of 0.6 mm, a LynxEye_XE_T array detector, and θ~2θ linked continuous scanning.
[0013] Preferably, when analyzing the crystalline phase impurity A, the scanning rate is 1° / minute, and the scanning 2θ angle range is 5°~18°; the characteristic diffraction peak 2θ angle of the crystalline phase impurity A is 6.6°±0.2°, and the characteristic diffraction peak 2θ angle of sodium zirconium cyclosilicate is 15.5°±0.2°.
[0014] Preferably, when analyzing the crystalline phase impurity B, the scanning rate is 0.04° / minute, and the scanning 2θ angle range is 13.5°~16°; the characteristic diffraction peak 2θ angle of the crystalline phase impurity B is 14.6°±0.2°, and the characteristic diffraction peak 2θ angle of sodium zirconium cyclosilicate is 15.5°±0.2°.
[0015] Preferably, the step width of the scanning is 0.02°.
[0016] Preferably, the mass fraction of the crystalline impurity reference substance in the standard curve sample is 1-25%.
[0017] The present invention provides an analysis method for crystalline phase impurities, comprising the following steps: obtaining an X-ray diffraction spectrum of a sodium zirconium cyclosilicate sample to be tested; obtaining the content of crystalline phase impurities in the sodium zirconium cyclosilicate sample to be tested according to a standard curve or standard equation of crystalline phase impurities and the X-ray diffraction spectrum of the sodium zirconium cyclosilicate sample to be tested; the standard curve is obtained by fitting the ratio of the mass of crystalline phase impurities and sodium zirconium cyclosilicate in the standard curve sample, and the ratio of the diffraction intensity of the characteristic diffraction peak of crystalline phase impurities and sodium zirconium cyclosilicate in the X-ray diffraction spectrum of the standard curve sample; the standard equation is a linear equation corresponding to the standard curve; the standard curve sample is a mixture of a blank sodium zirconium cyclosilicate sample and a crystalline phase impurity reference substance. The method provided by the present invention can be used to simply, quickly and accurately detect the content of crystalline phase impurities such as CPA and CPB in sodium zirconium cyclosilicate, and also has the advantages of wide linear range, good linear relationship, good precision, good durability and high detection sensitivity.
[0018] Furthermore, the sodium zirconium cyclosilicate sample to be tested in the present invention can be a powdered sample, and the X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested is a powder X-ray diffraction pattern, and the method for obtaining the powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested includes: using an X-ray diffractometer to scan the powdered sodium zirconium cyclosilicate sample to be tested to obtain the powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested; the standard curve sample can be a powdered sample, and the X-ray diffraction pattern of the standard curve sample is a powder X-ray diffraction pattern, and the method for obtaining the powder X-ray diffraction pattern of the standard curve sample includes: using an X-ray diffractometer to scan the powdered standard curve sample to obtain the powder X-ray diffraction pattern of the standard curve sample. The present invention adopts powder X-ray diffraction (PXRD) method, which can simply, quickly and accurately detect the content of crystalline impurity A (CPA) and crystalline impurity B (CPB) in sodium zirconium cyclosilicate (SCZ) when the sample is in a solid state, and also has the advantages of wide linear range, good linear relationship, good precision, good durability and high detection sensitivity.
[0019] The results of the embodiments show that the method of the present invention has high detection sensitivity. When analyzing and detecting the crystalline phase impurity CPA in SCZ, the minimum detection limit of CPA is about 0.20% (based on the mass fraction in SCZ); when analyzing and detecting the crystalline phase impurity CPB in SCZ, the minimum detection limit of CPB is about 0.86% (based on the mass fraction in SCZ). At the same time, the method of the present invention has a wide linear range and good linear relationship. When analyzing and detecting the crystalline phase impurity CPA in SCZ, CPA has a good linear relationship (r=0.9956) in the range of 2% to 20% of the mass fraction in the standard curve mixture; when analyzing and detecting the crystalline phase impurity CPB in SCZ, CPB has a good linear relationship (r=0.9988) in the range of 2% to 20% of the mass fraction in the standard curve mixture. Moreover, the method of the present invention has high accuracy. When analyzing and detecting the crystalline impurity CPA in SCZ, the recovery rates of CPA in the three concentrations of low, medium and high are all between 70% and 125%, and the RSDs are all less than 10.0%; when analyzing and detecting the crystalline impurity CPB in SCZ, the recovery rates of CPB in the three concentrations of low, medium and high are all between 70% and 125%, and the RSDs are all less than 10.0%. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the molecular structure diagram of sodium zirconium cyclosilicate; Figure 2 is the powder X-ray diffraction pattern of CPA; Figure 3 is the powder X-ray diffraction pattern of CPB; Figure 4 The PXRD spectrum obtained by detecting CPA under the CPA detection conditions in Example 1; Figure 5 The PXRD spectrum of SCZ obtained by testing under CPA testing conditions in Example 1; Figure 6 The PXRD spectrum obtained by testing the SCZ+CPA reference substance mixture under the CPA detection conditions in Example 1; Figure 7 The PXRD spectrum obtained by detecting CPB under the CPB detection conditions in Example 1; Figure 8 The PXRD spectrum of SCZ obtained by testing under CPB testing conditions in Example 1; Fig. 9 The PXRD spectrum of the SCZ+CPB reference substance mixture detected under the CPB detection conditions in Example 1; Fig.10 The standard curve and linear equation diagram of CPA; Fig.11Figure 2 is the standard curve and linear equation of CPB. DETAILED DESCRIPTION
[0021] The present invention provides a method for analyzing crystalline impurities, comprising the following steps: Obtaining an X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested; According to the standard curve or standard equation of the crystalline phase impurities and the X-ray diffraction spectrum of the sodium zirconium cyclosilicate sample to be tested, the content of the crystalline phase impurities in the sodium zirconium cyclosilicate sample to be tested is obtained; The standard curve is obtained by fitting according to the ratio of the mass of crystalline impurities and sodium zirconium cyclosilicate in the standard curve sample, and the ratio of the diffraction intensity of the crystalline impurities and the characteristic diffraction peak of sodium zirconium cyclosilicate in the X-ray diffraction spectrum of the standard curve sample; the standard equation is the linear equation corresponding to the standard curve; The standard curve sample is a mixture of a blank sodium zirconium cyclosilicate sample and a crystalline impurity reference substance.
[0022] Sodium zirconium cyclosilicate (SZC) is a drug originally developed by AstraZeneca for the treatment of hyperkalemia in adults. Its molecular structure is shown in the figure below. Figure 1 As shown. SCZ is prepared by a hydrothermal synthesis process using sodium hydroxide, colloidal silica, zirconium acetate and purified water under high temperature and high pressure conditions. During the synthesis of SCZ, impurities such as crystalline impurity A (CPA, specifically UZSi-8 in US5891417A) and crystalline impurity B (CPB, specifically UZSi-7 in US5891417A) may be generated due to insufficient stirring, thereby affecting the efficacy. However, there is currently no published literature reporting a method for detecting crystalline impurities such as CPA and CPB in SCZ. The method provided by the present invention can be used to simply, quickly and accurately detect the content of crystalline impurities such as CPA and CPB in sodium zirconium cyclosilicate. This is described in detail below.
[0023] The present invention obtains an X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested. The present invention adopts an X-ray diffraction method to determine the content of crystalline phase impurities in the sodium zirconium cyclosilicate sample; as an embodiment of the present invention, the crystalline phase impurities include crystalline phase impurities A and / or crystalline phase impurities B, specifically crystalline phase impurities A and crystalline phase impurities B. As an embodiment of the present invention, the sodium zirconium cyclosilicate sample to be tested can be a powdered sample, and the X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested is a powder X-ray diffraction pattern, and the method for obtaining the powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested includes: using an X-ray diffractometer to scan the powdered sodium zirconium cyclosilicate sample to be tested, and obtaining the powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested.
[0024] As an embodiment of the present invention, when analyzing the crystalline phase impurity A, the 2θ angle range of the scan can be 1~25°, and further can be 5°~18°; when scanning under the detection conditions of the crystalline phase impurity A, the characteristic diffraction peak 2θ angle of the crystalline phase impurity A can include 6.6°±0.2° (specifically 6.603° in the embodiment), and the characteristic diffraction peak 2θ angle of sodium zirconium cyclosilicate can include 11.9°±0.2°, 13.8°±0.2°, 15.5°±0.2° and 17.0°±0.2°, and can be specifically 15.5°±0.2° (specifically 15.501° in the embodiment).
[0025] As an embodiment of the present invention, when analyzing the crystalline phase impurity B, the 2θ angle range of the scan can be 10~20°, and further can be 13.5°~16°; when scanning under the detection conditions of the crystalline phase impurity B, the characteristic diffraction peak 2θ angle of the crystalline phase impurity B can include 14.6°±0.2° (specifically 14.605° in the embodiment), and the characteristic diffraction peak 2θ angle of sodium zirconium cyclosilicate can include 13.9°±0.2° and 15.5°±0.2°, and can specifically be 15.5°±0.2° (specifically 15.545° in the embodiment).
[0026] As an embodiment of the present invention, the scanning conditions may include: using a Bruker D8 X-ray diffractometer, using a Cu Kα target, a tube voltage of 40.0 kV, a tube current of 40.0 mA; a pre-Sola slit of 4.1°, a secondary Soller slit of 4°, a divergence slit of 0.6 mm, a LynxEye_XE_T array detector, and θ~2θ linkage continuous scanning. As an embodiment of the present invention, when analyzing the crystalline phase impurity A, the scanning rate may be 1° / minute, and the step width of the scanning may be 0.02°. As an embodiment of the present invention, when analyzing the crystalline phase impurity B, the scanning rate may be 0.04° / minute, and the step width of the scanning may be 0.02°.
[0027] As an embodiment of the present invention, the sodium zirconium cyclosilicate sample to be tested can be ground to obtain a powdered sodium zirconium cyclosilicate sample to be tested, and then scanned using an X-ray diffractometer to obtain a powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested; the present invention does not specifically limit the method and conditions of the grinding, as long as the requirements for scanning using an X-ray diffractometer are met. In an embodiment of the present invention, the X-ray diffractometer is calibrated before use; when using different X-ray diffractometers, the characteristic diffraction peak 2θ angles of various substances in the present invention will have a deviation of ±0.2°, which can be understood by those skilled in the art.
[0028] After obtaining the X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested, the present invention obtains the content of the crystalline phase impurities in the sodium zirconium cyclosilicate sample to be tested according to the standard curve or standard equation of the crystalline phase impurities and the X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested. In the present invention, the standard curve is obtained by fitting according to the ratio of the mass of the crystalline phase impurities and the sodium zirconium cyclosilicate in the standard curve sample, and the ratio of the diffraction intensity of the crystalline phase impurities and the characteristic diffraction peak of the sodium zirconium cyclosilicate in the X-ray diffraction pattern of the standard curve sample; the standard equation is the linear equation corresponding to the standard curve; the standard curve sample is a mixture of a blank sodium zirconium cyclosilicate sample and a crystalline phase impurity reference substance. As an embodiment of the present invention, the standard curve sample can be a powdered sample, the X-ray diffraction pattern of the standard curve sample is a powder X-ray diffraction pattern, and the method for obtaining the powder X-ray diffraction pattern of the standard curve sample includes: scanning the powdered standard curve sample with an X-ray diffractometer to obtain the powder X-ray diffraction pattern of the standard curve sample. As an embodiment of the present invention, the blank sodium zirconium cyclosilicate sample specifically refers to a sodium zirconium cyclosilicate sample that does not contain crystalline phase impurities. As an embodiment of the present invention, the mass fraction of the crystalline phase impurity reference substance in the standard curve sample can be 1~25%, further can be 2~20%, specifically can be 2%, 5%, 10%, 15% and 20%; in an embodiment of the present invention, when detecting crystalline phase impurity A, the standard curve sample is specifically a mixture of a blank sodium zirconium cyclosilicate sample and a crystalline phase impurity A reference substance, and the mass fraction of the crystalline phase impurity A reference substance in the standard curve sample can be specifically 2%, 5%, 10%, 15% and 20%; when detecting crystalline phase impurity B, the standard curve sample is specifically a mixture of a blank sodium zirconium cyclosilicate sample and a crystalline phase impurity B reference substance, and the mass fraction of the crystalline phase impurity B reference substance in the standard curve sample can be specifically 2%, 5%, 10%, 15% and 20%.
[0029] As an embodiment of the present invention, the horizontal coordinate of the standard curve is the ratio of the mass of the crystalline phase impurities and sodium zirconium cyclosilicate in the standard curve sample, and the vertical coordinate of the standard curve is the ratio of the diffraction intensity of the crystalline phase impurities and the characteristic diffraction peak of sodium zirconium cyclosilicate in the powder X-ray diffraction spectrum of the standard curve sample. In the embodiment of the present invention, specifically, each standard curve sample is scanned with an X-ray diffractometer according to the above method to obtain the powder X-ray diffraction spectrum of each standard curve sample, and the diffraction intensity of the characteristic diffraction peak of sodium zirconium cyclosilicate and the crystalline phase impurities in the powder X-ray diffraction spectrum of each standard curve sample is read out respectively, and the ratio of the mass of the crystalline phase impurities and sodium zirconium cyclosilicate in each standard curve sample is used as the horizontal coordinate, and the ratio of the diffraction intensity of the characteristic diffraction peak of the crystalline phase impurities and sodium zirconium cyclosilicate in the powder X-ray diffraction spectrum of each standard curve sample is used as the vertical coordinate to draw the standard curve. As an embodiment of the present invention, a blank sodium zirconium cyclosilicate sample can be mixed with a crystalline impurity reference substance and then ground to obtain a powdered standard curve sample, which is then scanned using an X-ray diffractometer to obtain a powder X-ray diffraction pattern of the standard curve sample; the present invention has no special limitations on the grinding method and conditions, as long as the requirements for scanning using an X-ray diffractometer are met.
[0030] As an embodiment of the present invention, after obtaining the powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested, the diffraction intensity of the crystalline phase impurities and the characteristic diffraction peak of sodium zirconium cyclosilicate in the powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested can be read out, and the ratio of the diffraction intensity of the crystalline phase impurities to the characteristic diffraction peak of sodium zirconium cyclosilicate is calculated respectively, and it is substituted into the linear equation corresponding to the standard curve, so that the content of the crystalline phase impurities in the sodium zirconium cyclosilicate sample to be tested can be calculated. As an embodiment of the present invention, the linear equation corresponding to the standard curve is as follows: y = ax + b ; in y is the ratio of the diffraction intensity of the crystalline impurities to the characteristic peak of sodium zirconium cyclosilicate in the powder X-ray diffraction spectrum of the standard curve sample, x is the ratio of the mass of crystalline impurities to sodium zirconium cyclosilicate in the standard curve sample, a is the slope, b is the intercept.
[0031] The method provided by the present invention can detect the content of crystalline impurity A (CPA) and crystalline impurity B (CPB) in sodium zirconium cyclosilicate (SCZ) when the sample is in a solid state. Specifically, after SCZ without CPA and CPB is ground into powder, different amounts of CPA or CPB are added, and the mixture is evenly mixed to prepare a series of standard curve samples. Each standard curve sample is scanned by an X-ray diffractometer, and a standard curve is drawn to obtain a linear equation. The SCZ to be tested is ground into powder and prepared into a test sample, and the sample is determined by the same method. The content of CPA or CPB in the SCZ to be tested is calculated by substituting the ratio of the peak diffraction intensity of CPA or CPB in the SCZ to be tested to the SCZ into the linear equation. The method provided by the present invention is used to analyze and detect the content of crystalline impurities CPA and CPB in SCZ, and the operation is simple, the linear range is wide, the linear relationship is good, the precision is good, the accuracy is high, the durability is good, and the detection sensitivity is high.
[0032] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The CPA used in the following experiments was prepared by referring to the method of UZSi-8 in patent US5891417A, and the CPB used was prepared by referring to the method of UZSi-7 in the patent, which are described in detail below.
[0034] The preparation method of CPA is as follows: 10.23 g of ZrOCl2·8H2O was dissolved in 109.38 g of deionized water to obtain a ZrOCl2 solution; 40.1 g of fumed silica, 409.68 g of 40 wt% tetrapropylammonium hydroxide and 42.58 g of sodium hydroxide were mixed, and the ZrOCl2 solution was added to the obtained mixed solution. The obtained white gel was homogenized in a stirrer for 4 minutes, then transferred to a polyethylene bottle, and aged at room temperature for 14 days; after the aging was completed, the obtained material was homogenized again in a stirrer for 3 minutes, and then transferred to a stainless steel hydrothermal synthesis reactor and reacted at 200° C. for 7 days; after the reaction was completed, the obtained product system was filtered under vacuum conditions, and the filter cake was collected, washed with deionized water and dried in air to obtain the CPA, whose powder X-ray diffraction pattern is as shown in Figure 2 shown.
[0035] The preparation method of CPB is as follows: 12.95 g of ZrOCl2·8H2O was dissolved in 20.4 g of deionized water to obtain a ZrOCl2 solution; under stirring, 5.12 g of fumed silica was added to a sodium carbonate solution prepared by 42.87 g of sodium carbonate and 106.5 g of deionized water. After the addition was completed, stirring was maintained, and the ZrOCl2 solution was added to the obtained mixed solution within 25 minutes. The obtained white gel was homogenized in a stirrer for 4 minutes, and then transferred to a stainless steel hydrothermal synthesis reactor and reacted at 200° C. for 7 days; after the reaction was completed, the obtained product system was filtered under vacuum conditions, and the filter cake was collected, washed with deionized water and dried in air to obtain the CPB, whose powder X-ray diffraction pattern is as shown in FIG. Figure 3 shown.
[0036] Example 1 CPA and CPB detection conditions CPA specificity test detection conditions: Bruker D8 X-ray diffractometer was used with Cu Kα target, tube voltage and tube current were 40.0 kV and 40.0 mA respectively; the pre-Sola slit was 4.1°, the secondary Soller slit was 4°, the divergence slit was 0.6 mm, the detector was LynxEye_XE_T array detector, θ~2θ linked continuous scanning, the scanning rate was 1° / min (0.02° step width), and the scanning range was 5°~18°.
[0037] CPB-specific test detection conditions: Bruker D8 X-ray diffractometer was used with Cu Kα target, tube voltage and tube current were 40.0 kV and 40.0 mA respectively; the pre-Sola slit was 4.1°, the secondary Soller slit was 4°, the divergence slit was 0.6 mm, the detector was LynxEye_XE_T array detector, θ~2θ linked continuous scanning, the scanning rate was 0.04° / min (0.02° step width), and the scanning range was 13.5°~16°.
[0038] Test steps: 1) CPA reference substance, 2) CPB reference substance, 3) SCZ, 4) SCZ+CPA reference substance mixture and 5) SCZ+CPB reference substance mixture were ground and sampled, and then PXRD scanning was performed and the spectra were recorded. The results are shown in Figure 4~Figure 9 .
[0039] Figure 4 This is the PXRD spectrum obtained by detecting CPA under the CPA detection conditions in Example 1. The results show that under the CPA detection conditions, the 2θ angle of the CPA characteristic diffraction peak is 6.603°.
[0040] Figure 5This is the PXRD spectrum of SCZ detected under CPA detection conditions in Example 1. The results show that under CPA detection conditions, the 2θ angle of the characteristic diffraction peak of SCZ is 15.501°.
[0041] Figure 6 This is the PXRD spectrum obtained by testing the SCZ + CPA reference mixture under the CPA detection conditions in Example 1. The results show that under the CPA detection conditions, the SCZ + CPA reference mixture has diffraction peaks at 2θ angles of 6.645° and 15.522°, and the two characteristic diffraction peaks of CPA and SCZ in the mixture are not interfered and can be used for analysis and detection.
[0042] Figure 7 This is the PXRD spectrum obtained by detecting CPB under the CPB detection conditions in Example 1. The results show that under the CPB detection conditions, the 2θ angle of the CPB characteristic diffraction peak is 14.605°.
[0043] Figure 8 This is the PXRD spectrum obtained by detecting SCZ under CPB detection conditions in Example 1. The results show that under CPB detection conditions, the 2θ angle of the characteristic diffraction peak of SCZ is 15.545°.
[0044] Fig. 9 This is the PXRD spectrum of the SCZ + CPB reference mixture detected under the CPB detection conditions in Example 1. The results show that under the CPB detection conditions, the SCZ + CPB reference mixture has diffraction peaks at 2θ angles of 14.602° and 15.543°, and the two characteristic diffraction peaks of CPB and SCZ in the mixture are not interfered and can be used for analysis and detection.
[0045] Example 2 CPA linear range a. The SCZ sample without CPA and CPB was fully ground to obtain a matrix; b. Add different masses of CPA to the matrix obtained in step a, grind and mix repeatedly, and prepare a series of standard curve samples, as follows: Linear 1 sample (20%): Take 0.4g matrix and 0.1g CPA reference substance, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and obtain; Linear 2 sample (15%): Take 0.425g matrix and 0.075g CPA reference substance, accurately weigh, put in the same mortar, grind and mix; Linear 3 sample (10%): Take 0.45g matrix and 0.05g CPA reference substance, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and obtain; Linear 4 sample (5%): Take 0.95g matrix and 0.05g CPA reference substance, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and obtain; Linear 5 sample (2%): Take 2.45g matrix and 0.05g CPA reference substance, weigh accurately, put them in the same mortar, grind them finely, mix them well, and obtain; c The standard curve samples prepared in step b were scanned by X- ray diffractometer to obtain PXRD spectra (related detection conditions refer to Example 1); d. Read out the diffraction intensities of the characteristic diffraction peaks of CPA and SCZ (6.6°±0.2° and 15.5°±0.2°, respectively) in the PXRD diffraction spectrum obtained in step c.
[0046] Table 1 shows the sample weights of matrix and CPA and their mass ratios when preparing standard curve samples, where m 对 / m 样 is the ratio of the mass of CPA and SCZ in the standard curve sample; Table 2 is the scanning results of the standard curve sample, wherein, I 对 is the diffraction intensity of the CPA characteristic diffraction peak of 6.6°±0.2° in the PXRD spectrum of the standard curve sample, I 样 is the diffraction intensity of the SCZ characteristic diffraction peak of 15.5°±0.2° in the PXRD spectrum of the standard curve sample, I 对 / I 样 It is the ratio of the diffraction intensity of the CPA 6.6°±0.2° characteristic diffraction peak and the SCZ 15.5°±0.2° characteristic diffraction peak in the PXRD spectrum of the standard curve sample.
[0047] Table 1 The weight of matrix and CPA and their mass ratio when preparing standard curve samples
[0048] Table 2 Scanning results of standard curve samples
[0049] The ratio of the diffraction intensity of the characteristic diffraction peaks of CPA and SCZ was linearly regressed against their mass ratio, and the standard curve of CPA was drawn to obtain the linear equation of CPA.
[0050] Fig.10 Figure 3 is the standard curve and linear equation diagram of CPA. The results show that when the mass fraction of CPA in SCZ is in the range of 2~20%, the ratio of the diffraction intensity of the characteristic diffraction peaks of CPA and SCZ has a good linear relationship with the mass ratio of the two, and the linear equation is: y=0.6572x-0.0101 (r=0.9956).
[0051] Example 3 CPB linear range a. The SCZ sample without CPA and CPB was fully ground to obtain a matrix; b. Different masses of CPB were added to the matrix obtained in step a, and the mixture was repeatedly ground and mixed to prepare a series of standard curve samples, as follows: Linear 1 sample (20%): Take 0.4g matrix and 0.1g CPB reference substance, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and obtain; Linear 2 sample (15%): Take 0.425g matrix and 0.075g CPB reference substance, accurately weigh, put in the same mortar, grind finely, mix well, and obtain; Linear 3 sample (10%): Take 0.45g matrix and 0.05g CPB reference substance, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and obtain; Linear 4 sample (5%): Take 0.95g matrix and 0.05g CPB reference substance, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and obtain; Linear 5 sample (2%): Take 2.45g matrix and 0.05g CPB reference substance, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and obtain; c The standard curve samples prepared in step b were scanned by X- ray diffractometer to obtain PXRD spectra (related detection conditions refer to Example 1); d. Read out the diffraction intensities of the characteristic diffraction peaks of CPB and SCZ (14.6°±0.2° and 15.5°±0.2°, respectively) in the PXRD diffraction spectrum obtained in step c.
[0052] Table 3 shows the sample weights of matrix and CPB and their mass ratios when preparing standard curve samples, where m 对 / m 样 is the ratio of the mass of CPB and SCZ in the standard curve sample; Table 4 is the scanning result of the standard curve sample, wherein I 对 is the diffraction intensity of the CPB characteristic diffraction peak 14.6°±0.2° in the PXRD spectrum of the standard curve sample, I 样 is the diffraction intensity of the SCZ characteristic diffraction peak of 15.5°±0.2° in the PXRD spectrum of the standard curve sample, I 对 / I 样 It is the ratio of the diffraction intensity of the CPB14.6°±0.2° characteristic diffraction peak and the SCZ 15.5°±0.2° characteristic diffraction peak in the PXRD spectrum of the standard curve sample.
[0053] Table 3 The mass of matrix and CPB and their mass ratio when preparing standard curve samples
[0054] Table 4 Scanning results of standard curve samples
[0055] The ratio of the diffraction intensity of the characteristic diffraction peaks of CPB and SCZ was linearly regressed against their mass ratio, and a standard curve of CPB was drawn to obtain the linear equation of CPB.
[0056] Fig.11 The standard curve and linear equation diagram of CPB show that when the mass fraction of CPB in SCZ is in the range of 2% to 20%, the ratio of the diffraction intensity of the characteristic diffraction peaks of CPB and SCZ has a good linear relationship with the mass ratio of the two, and the linear equation is: y=0.1661x-0.0002 (r=0.9988).
[0057] Example 4 CPA recovery rate High-concentration recovery sample: Take 0.425g matrix and 0.075g CPA, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and prepare 3 copies in parallel; Medium concentration recovery sample: Take 0.45g matrix and 0.05g CPA, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and prepare 3 copies in parallel; Low-concentration recovery sample: Take 0.95g matrix and 0.05g CPA, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and prepare 3 copies in parallel; The samples were tested according to the relevant test conditions in Example 1, and the CPA content was calculated according to the standard curve of CPA in Example 2.
[0058] Table 5 shows the results of the CPA recovery test. It can be seen that the recoveries of CPA at three concentrations, low, medium and high, are all between 70% and 125%, and the RSDs are all less than 10.0%.
[0059] Table 5 CPA recovery rate
[0060] Example 5 CPB recovery rate High-concentration recovery sample: Take 0.425g matrix and 0.075g CPB, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and prepare 3 copies in parallel; Medium concentration recovery sample: Take 0.45g matrix and 0.05g CPB, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and prepare 3 copies in parallel; Low-concentration recovery sample: Take 0.95g matrix and 0.05g CPB, weigh accurately, put them in the same mortar, grind them into powder, mix them evenly, and prepare 3 copies in parallel.
[0061] The sample was tested according to the relevant test conditions in Example 1, and the CPB content was calculated according to the standard curve of CPB in Example 3.
[0062] Table 6 shows the results of the CPB recovery test. It can be seen that the recoveries of the three concentrations of CPB, low, medium and high, are all between 70% and 125%, and the RSDs are all less than 10.0%.
[0063] Table 6 CPB recovery rate
[0064] Example 6 CPA detection limit Detection limit sample: Take 2.45g matrix and 0.05g CPA reference substance, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and obtain the sample.
[0065] Take the above samples, collect the PXRD spectra of the samples, scan each sample once, read the diffraction intensity at the characteristic diffraction peak positions of 6.6°±0.2° and 15.5°±0.2° in the spectrum, and record them as I 对 and I 样 , calculate the ratio of the diffraction intensity response value of CPA to the diffraction intensity of sodium zirconium cyclosilicate (I 对 / I 样 ), and then calculate the standard deviation (δ) of 10 samples, and calculate the detection limit according to the following formula: Limit of detection (LOD) = 3.3δ / S × 100; Where S is the slope of the standard curve of CPA.
[0066] The specific results are shown in Table 7. The results showed that the detection limit of CPA was 0.20%.
[0067] Table 7 CPA detection limit
[0068] Example 7 CPB detection limit Detection limit sample: Take 2.45g matrix and 0.05g CPB reference substance, weigh accurately, put them in the same mortar, grind them finely, mix them evenly, and obtain the sample.
[0069] Take the above samples, collect the PXRD spectra of the samples, scan each sample once, read the diffraction intensity at the characteristic diffraction peak positions of 14.6°±0.2° and 15.5°±0.2° in the spectra, and record them as I 对 and I 样, calculate the ratio of the diffraction intensity response value of CPB to the diffraction intensity of sodium zirconium cyclosilicate (I 对 / I 样 ), and then calculate the standard deviation (δ) of 10 samples, and calculate the detection limit according to the following formula: Limit of detection (LOD) = 3.3δ / S × 100; Where S is the slope of the standard curve of CPB.
[0070] The specific results are shown in Table 8. The results show that the detection limit of CPB is 0.86%.
[0071] Table 8 CPB detection limit
[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for analyzing crystalline impurities, comprising the following steps: Obtaining an X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested; According to the standard curve or standard equation of the crystalline phase impurities and the X-ray diffraction spectrum of the sodium zirconium cyclosilicate sample to be tested, the content of the crystalline phase impurities in the sodium zirconium cyclosilicate sample to be tested is obtained; The standard curve is obtained by fitting according to the ratio of the mass of crystalline impurities and sodium zirconium cyclosilicate in the standard curve sample, and the ratio of the diffraction intensity of the crystalline impurities and the characteristic diffraction peak of sodium zirconium cyclosilicate in the X-ray diffraction spectrum of the standard curve sample; the standard equation is the linear equation corresponding to the standard curve; The standard curve sample is a mixture of a blank sodium zirconium cyclosilicate sample and a crystalline impurity reference substance.
2. The analysis method according to claim 1, characterized in that The sodium zirconium cyclosilicate sample to be tested is a powder sample, the X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested is a powder X-ray diffraction pattern, and the method for obtaining the powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested comprises: scanning the powdered sodium zirconium cyclosilicate sample to be tested by an X-ray diffractometer to obtain the powder X-ray diffraction pattern of the sodium zirconium cyclosilicate sample to be tested; The standard curve sample is a powdered sample, and the X-ray diffraction pattern of the standard curve sample is a powder X-ray diffraction pattern. The method for obtaining the powder X-ray diffraction pattern of the standard curve sample includes: using an X-ray diffractometer to scan the powdered standard curve sample to obtain the powder X-ray diffraction pattern of the standard curve sample.
3. The analysis method according to claim 2, characterized in that The crystalline phase impurities include crystalline phase impurities A and / or crystalline phase impurities B; when analyzing the crystalline phase impurities A, the 2θ angle range of the scan is 1 to 25°; when analyzing the crystalline phase impurities B, the 2θ angle range of the scan is 10 to 20°.
4. The analysis method according to claim 3, characterized in that When scanning is performed under the detection conditions of the crystalline phase impurity A, the characteristic diffraction peak 2θ angles of the crystalline phase impurity A include 6.6°±0.2°, and the characteristic diffraction peak 2θ angles of sodium zirconium cyclosilicate include 11.9°±0.2°, 13.8°±0.2°, 15.5°±0.2° and 17.0°±0.2°.
5. The analysis method according to claim 3, characterized in that When scanning is performed under the detection conditions of the crystalline phase impurity B, the characteristic diffraction peak 2θ angles of the crystalline phase impurity B include 14.6°±0.2°, and the characteristic diffraction peak 2θ angles of sodium zirconium cyclosilicate include 13.9°±0.2° and 15.5°±0.2°.
6. The analysis method according to any one of claims 2 to 5, characterized in that The scanning conditions include: using a Bruker D8 X-ray diffractometer, a Cu Kα target, a tube voltage of 40.0 kV, a tube current of 40.0 mA; a pre-Sola slit of 4.1°, a secondary Soller slit of 4°, a divergence slit of 0.6 mm, a LynxEye_XE_T array detector, and θ~2θ linked continuous scanning.
7. The analysis method according to claim 6, characterized in that When analyzing the crystalline phase impurity A, the scanning rate is 1° / minute, and the scanning 2θ angle range is 5°~18°; the characteristic diffraction peak 2θ angle of the crystalline phase impurity A is 6.6°±0.2°, and the characteristic diffraction peak 2θ angle of sodium zirconium cyclosilicate is 15.5°±0.2°.
8. The analysis method according to claim 6, characterized in that When analyzing the crystalline phase impurity B, the scanning rate is 0.04° / min, and the scanning 2θ angle range is 13.5°~16°; the characteristic diffraction peak 2θ angle of the crystalline phase impurity B is 14.6°±0.2°, and the characteristic diffraction peak 2θ angle of sodium zirconium cyclosilicate is 15.5°±0.2°.
9. The analysis method according to claim 7 or 8, characterized in that The step width of the scan was 0.02°.
10. The analysis method according to claim 1, characterized in that The mass fraction of the crystalline impurity reference substance in the standard curve samples is 1-25%.
Citation Information
Patent Citations
Microporous zirconium silicate for treating hyperkalemia
CN104797263A
Microporous zirconium silicate for the treatment of hyperkalemia in hypercalcemic patients and improved calcium-containing compositions for the treatment of hyperkalemia
CN104968336A
Method for detecting phase purity of lithium titanate composition
CN106053500A
Method for detecting basic lanthanum carbonate impurities in lanthanum carbonate raw material or preparation thereof in solid state
CN110579499A
Microporous zirconium silicate for the treatment of hyperkalemia
US20140113002A1
Cited By
A sodium zirconium cyclosilicate crystalline form impurity b and a method of preparation thereof
CN122725295A